2010
DOI: 10.1186/1475-925x-9-82
|View full text |Cite
|
Sign up to set email alerts
|

Kalman estimator- and general linear model-based on-line brain activation mapping by near-infrared spectroscopy

Abstract: BackgroundNear-infrared spectroscopy (NIRS) is a non-invasive neuroimaging technique that recently has been developed to measure the changes of cerebral blood oxygenation associated with brain activities. To date, for functional brain mapping applications, there is no standard on-line method for analysing NIRS data.MethodsIn this paper, a novel on-line NIRS data analysis framework taking advantages of both the general linear model (GLM) and the Kalman estimator is devised. The Kalman estimator is used to updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 46 publications
0
98
0
Order By: Relevance
“…The use of a model-based fNIRI analysis approach by means of the general linear model (GLM) methodology (Bullmore et al, 1996;Friston et al, 1995;Worsley and Friston, 1995) was reported by several authors (e.g. Boas et al, 2003;Çiftçi et al, 2008;Fekete et al, 2011;Hu et al, 2010;Imai et al, 2012;Koh et al, 2007;Moriai-Izawa et al, 2012;Plichta et al, 2007a,b;Schroeter et al, 2004;Tsuzuki et al, 2012;Ye et al, 2009). GLM is a statistical linear model explaining data as a linear combination of an explanatory variable plus an error term.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
See 1 more Smart Citation
“…The use of a model-based fNIRI analysis approach by means of the general linear model (GLM) methodology (Bullmore et al, 1996;Friston et al, 1995;Worsley and Friston, 1995) was reported by several authors (e.g. Boas et al, 2003;Çiftçi et al, 2008;Fekete et al, 2011;Hu et al, 2010;Imai et al, 2012;Koh et al, 2007;Moriai-Izawa et al, 2012;Plichta et al, 2007a,b;Schroeter et al, 2004;Tsuzuki et al, 2012;Ye et al, 2009). GLM is a statistical linear model explaining data as a linear combination of an explanatory variable plus an error term.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…GLM is a statistical linear model explaining data as a linear combination of an explanatory variable plus an error term. How to combine GLM with a Kalman estimator and to analyze fNIRI data was shown by Hu et al (2010). Methods using independent component analysis (ICA) (Akgül et al, 2006;Katura et al, 2008;Kohno et al, 2007;Markham et al, 2009;Medvedev et al, 2008;Morren et al, 2004;Schelkanova and Toronov, 2012) or principal component analysis (PCA) H.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…1), which receives r ftg as input and uses r ft−1g to r ft−Pg as predictors. Equations (4)- (13) are then used to update the AR coefficients in the second Kalman model. Similar to the first Kalman model, the state update matrix (A) is identity (e.g., a random walk model).…”
Section: A Kalman Estimatormentioning
confidence: 99%
“…Due to the portability and high sample rate of fNIRS measurements, several researchers have previously explored the use of fNIRS in real-time assessments of brain activity, [10][11][12][13][14][15][16][17] biofeedback, 18 and brain-computer interfacing applications. 15,16,[19][20][21][22][23][24] These real-time applications, however, must contend with noise and artifacts often contained within the NIRS data.…”
Section: Introductionmentioning
confidence: 99%
“…But whereas some physiological noises (i.e., respiratory and cardiac activities) can be removed using a low-pass filter (LPF), 20 low-frequency (e.g., 0.15 Hz) oscillatory noises and motion artifacts cannot. Alternatively, unwanted noises and artifacts from fNIRS signals can be removed using linear regression, 21 least mean squares adaptive filtering, 22 and ICA. [23][24][25][26] Continuous-wave-type fNIRS measures the optical intensity changes 27 at two wavelengths, 28 which results are then converted to hemodynamic concentration changes using the modified Beer-Lambert law.…”
Section: Introductionmentioning
confidence: 99%